Integrating physical activity in mathematics lessons: A pilot study - Černigoj, Erika; Volmut, Tadeja (Annales Kinesiologiae, 2022)
Introduction: The aim of the study was to investigate the effect of teaching mathematics through movement, depending on the amount and intensity of physical activity or the time of physical inactivity during school hours and, particular, during mathematics lessons. Methods: Twenty-two sixth graders from a Slovenian primary school participated in the study. The experimental group consisted of 16 students and the control group consisted of 6 students. Mathematics lessons were planned together with the mathematics teacher. This was then carried out in the experimental group. In the control group, the mathematics lessons remained unchanged. The intervention lasted for one week. For the duration of the experiment, students wore an accelerometer on their right hip during school hours. Results: We found that the experimental group engaged in moderate to vigorous intensity physical activity for 7.8 minutes more during mathematics lessons (P < 0.001) than the control group. In addition, the experimental group was less physically inactive during math lessons for 6.7 minutes (P = 0.001) than control group. Physical activity during school hours did not differ between groups (P = 0.284). Nevertheless, the experimental group spent slightly more time at moderate to vigorous intensity during school hours than the control group and was less physically inactive. Conclusion: This study showed that integrating physical activity with mathematics in the academic classroom results in increased moderate to vigorous physical activity compared to a traditional classroom. Further research should be conducted to determine how integrating physical activity with various school subjects affects daily physical activity in children and adolescents.